The Impact of Construction Management Patterns on Housing Quality in Housing Residences - Muhammad Yusuf Ali; Sylviana Maya Damayanti; Mulya Amri (Universitas Mercu Buana, 2026)
This study examines how construction management patterns, self-performance versus subcontracting, and Project Manager (PM) leadership relate directly to housing quality in a residential project. Using a case study of the Vila Rizki Insani development (IDR 3,800,000/m²), a mixed-method approach integrated unit-level complaint records during a 90-day retention window, pre-handover homecare checklists for ready-stock units, project documents, and semi-structured interviews with PMs, foremen, and estate staff. Quantitative analysis compared the outcomes across two contractors: a self-performing contractor delivering 297 units and a subcontracting contractor delivering 106 units. Self-performing output showed lower normalized complaint rates (minor 2.36%, moderate 2.36%) but included a small incidence of serious defects (0.34%), whereas subcontracting showed a higher minor-complaint rate (8.4%), lower moderate complaints (1.88%), and no serious cases recorded during retention period. Qualitative findings indicate that contracting schemes structure accountability and inspection routines, shaping the PM’s practical leverage over workmanship; transactional control is easier to operationalize under self-performing teams, whereas fragmented trade packages in subcontracting increase interface gaps and finishing rework risk. Overall, contracting schemes and workforce capacity emerged as primary drivers of quality consistency under tight pricing, with complaint response speed influencing perceived quality. The study recommends aligning work packages with supervision capacity and formalizing inspection and post-sales response routines.